Endothelial Lipase Activity Predicts High-Density Lipoprotein Catabolism in Hemodialysis - Miksztowicz, Veronica Julieta (2012)
Objective: A novel phospholipase assay was used to measure for the first time the behavior of endothelial and hepatic phospholipase activities in postheparin human plasma of hemodialyzed patients and its relationship with atherogenic and antiatherogenic lipoprotein levels.Methods and Results:Endothelial and hepatic phospholipase activity was assessed in a total SN1-specific phospholipase assay, using (1-decanoylthio-1-deoxy-2-decanoyl-sn-glycero-3-phosphoryl) ethylene glycol as the substrate. Hemodialyzed patients presented lower values of total and hepatic phospholipase activity than controls: 4.4 (1.9?9.0) versus 7.5 (3.6-18.0) and 2.6 (0.7-6.2) versus 6.6 (1.3-15.2) μmol of fatty acid released per milliliter of postheparin plasma per hour, respectively (P<0.001); however, endothelial lipase (EL) phospholipase activity was increased in patients: 1.7 (0.8-3.0) versus 1.1 (0.1-2.7) μmol of fatty acid released per milliliter of postheparin plasma per hour (P=0.008). EL was negatively associated with high-density lipoprotein (HDL)-cholesterol (r=-0.427; P=0.001), and apolipoprotein A-I levels, total phospholipase, and hepatic lipase activity were directly associated with low-density lipoprotein-cholesterol and apolipoprotein B. The association of EL and HDL-cholesterol remained significant when adjusting for waist circumference (β=-0.26; P=0.05), and the effect of hepatic lipase on low-density lipoprotein-cholesterol continued after adjusting for age (β=0.46; P= 0.001).Conclusion: Our results support the hypothesis that EL is the predominant enzyme responsible for lipolytic catabolism of HDLs in hemodialyzed patients and resolve the apparent paradox observed between low hepatic lipase activity and decreased HDL-cholesterol levels observed in these patients. In addition, the ability to assess total hepatic lipase and EL phospholipase activity in plasma will increase our knowledge of the mechanisms involved in controlling HDL levels and cardiovascular risk in hemodialyzed patients, as well as other populations with low levels of HDL-cholesterol.